Solidaridad, territorio y aprendizaje colectivo en los conflictos urbanos: la Asamblea General de los Pueblos, Barrios, Colonias y Pedregales de Coyoacán - Sierra Martínez, Andrés (El Colegio de México A.C., 2022)
This paper analyzes the emergence of solidarity networks and collective learning spaces as one of the consequences of urban socio-environmental conflicts. It works with the case of the General Assembly of Peoples, Neighborhoods, Communities and Pedregales of Coyoacán, an organization that emerges in a conflict over the environmental damage caused by a real estate project south of Mexico City. It is argued that solidarity networks and collective learning are part of a territorialization process with expectations of environmental justice mobilized in protest.